Cyclic loading tests of self-centering prestressed prefabricated steel beam-column joint with weakened FCP. (1st February 2022) - Jiang, Zi-Qin; Chen, Mei-Lin; Yang, Zhong-Shuai; Li, Xiang-Yuan; Cai, Chao
Highlights: A type of earthquake-resilient SPPSJ with dog bone weakened FCP is proposed. The FCP dissipates energy and prestressed cable realizes self-centering. Reasonable cable pretension and FCP thickness can achieve ideal self-centering. The joint with dog bone weakened FCP has better energy dissipation capacity. SPPSJ has superior bearing capacity, seismic performance and self-centering capacity. Abstract: Earthquake-resilient structures are an ideal new direction for seismic design of structures. In recent years, earthquake-resilient structures have gradually become a research hotspot in seismic field. Based on the idea of damage control, this paper proposes a self-centering prestressed prefabricated steel beam-column joint (SPPSJ) with dog bone weakened flange cover plate (FCP). By designing three sets of test specimens for cyclic loading test, the thickness of the dog bone weakened FCP and the pretension of the cable were studied, and the hysteresis curve, skeleton curve and cumulative energy dissipation curve of the joint were obtained. Then, the reliability of the test results is verified by numerical analysis. Finally, the design proposals of SPPSJ are put forward, which is convenient for the popularization and use of SPPSJ. The results show that: The SPPSJ has good bearing capacity, seismic performance and self-centering capacity after earthquake, which can effectively dissipate energy through plastic deformation of FCP, and realize post-earthquake resetting of the joint through prestressed cables. On the premise of the same load-bearing capacity, it can obtain that the SPPSJs with dog bone weakened FCP have better energy dissipation performance and lower requirement cable pretension, which makes the prestressed cable maintain high safety factor during the loading process. There is a certain range of correspondence between the thickness of the dog bone weakened FCP and the cable pretension. When the yield load ratio of the dog bone weakened FCP to high-strength bolts on web connection plates and the cables is about 3/7, the energy dissipation capacity and self-centering capacity of the SPPSJ can reach the best balance.